Discovery of potential cyclooxygenase inhibitors using in silico docking studies (Bangladesh Journal of Pharmacology, 2012)
This study deals with the evaluation of the cyclooxygenase inhibitory activity of flavonoids (tangeritin, morin, rhamnetin, theaflavin, pachypodol, eriodictyol, homoeriodictyol, aromadedrin, okanin) using in silico docking studies. In silico docking studies were carried out using AutoDock 4.2. Three important parameters like binding energy, inhibition constant and intermolecular energy were determined. The results showed that all the selected flavonoids showed binding energy ranging between -8.77 kcalmol-1 to -6.10 kcalmol-1 when compared with that of the standard (-8.30 kcalmol-1). Intermolecular energy (-10.56 kcalmol-1 to -7.89 kcalmol-1) and inhibition constant (373.91 nM to 34.03 µM) of the ligands also coincide with the binding energy. All the selected flavonoids contributed cyclooxygenase inhibitory activity because of its structural parameters. These molecular docking analyses could lead to the further development of potent cyclooxygenase inhibitors.